Carbon nitride-based photocatalytic composite membrane as well as preparation method and application thereof
Through the combination of electrospinning process of carbon nitride-based photocatalytic composite film and photocatalytic materials, the existing films have solved the problem of insufficient performance in oil-water separation and purification, and achieved efficient on-demand separation and dye degradation effects.
Patent Information
- Application Number
- CN202411866761.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing oil-based wastewater treatment membranes have problems such as large external driving force demand, poor anti-pollution performance, and limited ability to remove organic and microbial pollutants in oil-water separation and purification. The fixed super-wetted membranes cannot adapt to variable conditions and need.
Carbon nitride-based photocatalytic composite film is used to form an intelligent separation of hybrid matrix membrane on demand through electrospinning process, which can switch between underwater superolipidity and underolipidity, and combine the degradation ability of photocatalytic materials to achieve Highly efficient oil-water separation and dye degradation.
It has achieved the switching of superspliability through a simple prewetting strategy under gravity, achieving a 99% oil-water separation efficiency, and restoring the separation flux under light, with self-cleaning ability, and the dye degradation rate can reach 99.99%.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental multifunctional materials, and specifically relates to a carbon nitride-based photocatalytic composite film and a preparation method and application thereof. Background Art
[0002] The discharge of industrial oily wastewater poses significant risks to ecosystems and human health, while exacerbating the depletion of precious freshwater resources. Membrane separation technology has become an effective solution for treating oily wastewater due to its ease of operation, high efficiency and environmental sustainability. In particular, superwetting membranes with high affinity for water or oil have become key materials for achieving selective oil-water separation. However, these membranes still face challenges, such as the need for large external driving forces, insufficient anti-fouling performance, and limited ability to remove organic and microbial pollutants. These issues have become major obstacles to the effective separation and purification of complex oily wastewater. In addition, separation membranes are often required to adapt to changing conditions and requirements in practical applications. However, membranes with fixed superwetting properties have limitations, and their single wettability limits the ability to use a single material to alternately remove oil and water. The development of separation membranes with switchable superwetting properties is essential to meet the needs of oil-water separation processes. Using a single separation material to achieve switchable superwetting has significant advantages, especially in reducing raw material waste and providing a smarter alternative to traditional materials. In recent years, advanced superwetting materials with switchable wettability have become the focus of extensive attention, which can achieve highly selective and on-demand oil-water separation. Smart surfaces triggered by external stimuli (such as pH, gas, voltage, or temperature) have been considered as a key strategy to achieve reversible and switchable wettability. However, the complexity of wetting transition and preparation process has become a major challenge for its widespread application.
[0003] Therefore, the development of oil-water separation membrane materials that can exhibit underwater super-amphiphobic properties only through liquid pre-wetting has become one of the current research hotspots. It is worth noting that these smart membrane surfaces achieve opposite underwater wettability through pre-wetting and maintain a stable liquid infiltration layer, effectively preventing the penetration of the opposing liquid phase. Therefore, underwater super-amphiphobic materials have significant advantages in highly controllable and selective oil-water separation.
[0004] The complexity of the oil wastewater system is not only reflected in the separation of oil-water emulsions, but also includes the presence of other harmful substances in the wastewater. The discharge of wastewater containing dyes has become another important issue of water pollution. Many dyes have strong chromaticity and toxicity, which have a significant impact on aquatic organisms and the environment. If they are discharged directly without effective treatment, they will further harm water resources and the ecological environment. Therefore, in addition to oil-water separation, how to effectively remove toxic dyes from wastewater has also become one of the important challenges facing current water treatment technology.
[0005] In recent years, two-dimensional layered photocatalytic materials including g-C3N4, MXene and graphene have shown broad application prospects in the field of membrane separation due to their rich terminal groups, excellent photothermal synergistic effect, superior photocatalytic performance, excellent hydrophilicity, and good combination with electrospun nanofiber membranes. As an environmentally friendly metal-free two-dimensional π-conjugated material, the rich amino groups in g-C3N4 give it excellent hydrophilicity, which effectively regulates water channels and enhances the separation flux and separation efficiency of emulsions. In addition, considering the issues of environmental protection and sustainable development, the research team prefers to use low-cost, environmentally friendly and durable carbon nitride-based materials and biodegradable and environmentally friendly membrane substrates to prepare oil-water separation membranes. The technology of combining photocatalytic materials with fiber membranes has broad application prospects in the degradation of methylene blue. It can not only improve the degradation efficiency, but also achieve more sustainable water treatment by reducing catalyst loss, extending catalyst service life and improving material stability. Summary of the invention
[0006] The object of the present invention is to provide a carbon nitride-based photocatalytic composite film, the prepared composite film has unique air super-amphiphilicity and liquid super-amphiphobicity, and can be switched between underwater super-oleophobicity and oil-under-super-hydrophobicity through a simple pre-wetting strategy to achieve efficient on-demand separation of water-in-oil emulsion / water-in-oil emulsion and show good separation performance and good circulation performance. In addition, the film has a good dye degradation function and has excellent degradation ability for dyes under visible light. Therefore, the composite film can be used for wastewater separation and purification and other applications.
[0007] In a first aspect, the present invention provides a method for preparing a carbon nitride-based photocatalytic composite film, which is specifically carried out according to the following steps: (1) Preparation of modified CCN photocatalytic materials Hexadecyltrimethylammonium bromide (CTAB) was dissolved in water, melamine was added, and ultrasonic dispersion was uniformly performed to obtain a mixed solution; the mixed solution was hydrothermally reacted at 150°C for 6-24 h. After the reaction, the product was taken out, washed three times by alternating centrifugation with ultrapure water and anhydrous ethanol, dried at 70-80°C and ground into powder. Then, the powder was placed in a muffle furnace and calcined at 500-600°C for 4 h at a heating rate of 5°C / min in an air atmosphere to obtain the product modified carbon nitride (CCN).
[0008] Wherein, the mass ratio of CTAB to melamine is 0.3 to 0.9:3, preferably 0.6 to 0.9:3, and more preferably 0.6:3.
[0009] The calcination temperature is preferably 550°C.
[0010] (2) Preparation of PCL@CCN composite film CCN powder was dispersed in N,N, dimethylformamide (DMF) and ultrasonically treated for 1 h to obtain suspension A. Polycaprolactone (PCL) was added to DMF and stirred at 60 °C until completely dissolved to obtain solution B. Subsequently, suspension A was poured into solution B and stirred evenly to form a uniform light yellow spinning solution. The prepared spinning solution was transferred to a syringe and electrospun at a positive voltage of 10~12 kV for 8~10 h. The feed rate of the spinning solution was set to 0.8~1 mL / h, the distance from the needle to the roller collector was 10~13 cm, and the roller speed was 90 rpm. During the experiment, the temperature was maintained at 25±5 °C and the humidity was controlled at 30±5%. Finally, the prepared electrospun membrane was dried at 45 °C for 12 h to obtain a PCL@CCN composite membrane.
[0011] Among them, the mass ratio of CCN, PCL and DMF is 0.1~0.5:0.5~2:9~10.
[0012] Preferably, the electrospinning is performed at a positive voltage of 10.8 kV, the spinning time is 8 h, the feeding rate of the spinning solution is set to 0.8 mL / h, the distance from the needle to the roller collector is 13 cm, and the roller speed is 90 rpm.
[0013] The diameter of a single nanofiber in the organic polymer composite fiber membrane produced by electrospinning is 100~600 nm.
[0014] (3) Preparation of HPCL@CCN carbon nitride-based photocatalytic composite film The membrane was cut into appropriate size, immersed in NaOH solution, and oscillated in an oscillation box at 37 °C for 0.1-1 h to obtain the HPCL@CCN membrane. Finally, the HPCL@CCN composite membrane was dried at 45 °C for 6 h.
[0015] The concentration of the NaOH solution is 1 M.
[0016] The composite membrane prepared by the present invention can switch between underwater superoleophobicity and oil-under-oil superhydrophobicity only under the action of gravity through a simple pre-wetting strategy to achieve efficient on-demand separation of water-in-oil emulsion / oil-in-water emulsion. When the membrane is wetted with water, the composite membrane can efficiently separate water-in-oil emulsion (isolate oil droplets and separate water droplets); on the contrary, when the membrane is wetted with oil, the composite membrane can efficiently separate oil-in-water emulsion (isolate water droplets and separate oil droplets). The composite membrane of the present invention is used for on-demand separation of water-in-oil emulsion / oil-in-water emulsion; and can restore the separation flux under light, thereby having self-cleaning ability.
[0017] The composite film of the invention is used for degrading methylene blue dye under low-power visible light irradiation.
[0018] The technical effects of the present invention are: (1) An intelligent on-demand separation mixed matrix membrane was formed by electrospinning. The resulting HPCL@CCN composite membrane exhibited unique air super-amphiphobicity and underwater super-hydrophobicity. The molecular structure of HPCL contains both hydrophilic (-COOH) and hydrophobic (-CH2) groups, which is conducive to the preparation of underwater super-amphiphobic surface.
[0019] (2) The HPCL@CCN composite membrane has a high separation efficiency (99%) for surfactant-stabilized water-in-oil emulsions / oil-in-water emulsions under gravity separation, and can alternately separate water-in-oil emulsions / oil-in-water emulsions after rinsing and drying with ethanol, with a separation efficiency of about 99%.
[0020] (3) Under illumination, the HPCL@CCN composite membrane has a higher flux recovery rate (90%), higher reversible pollution resistance (68%), and lower irreversible pollution resistance (32%) due to the photocatalytic properties of CCN.
[0021] (4) Under the action of H2O2 combined with light, CCN can effectively activate H2O2 under visible light irradiation to produce additional active free radicals, which have the ability to rapidly degrade MB (methylene blue) dye. The dye degradation rate can reach 99.99% after 90 min of light irradiation. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 X-ray diffraction (XRD) diagrams of CCN and CN nanomaterials prepared in Example 1 of the present invention.
[0023] Figure 2 This is a scanning electron microscope (SEM) image of the PCL@CCN nanofiber membrane prepared in Example 1 of the present invention.
[0024] Figure 3 This is a scanning electron microscope (SEM) image of the HPCL@CCN nanofiber membrane prepared in Example 1 of the present invention.
[0025] Figure 4 Graphs showing the underwater oil contact angle and the underwater water contact angle of the HPCL@CCN nanofiber membrane prepared in Example 1 of the present invention.
[0026] Figure 5 This is a diagram of the separation efficiency of the HPCL@CCN nanofiber membrane prepared in Example 1 of the present invention for alternately cyclically separating oil-in-water emulsion / water-in-oil emulsion.
[0027] Figure 6This is a graph showing the flux recovery rate, reversible pollution resistance and irreversible pollution resistance results of the HPCL@CCN nanofiber membrane prepared in Example 1 of the present invention under light. DETAILED DESCRIPTION
[0028] The present invention is described in detail below with reference to specific embodiments. Example 1
[0029] 1. Preparation of HPCL@CCN composite membrane (1) Preparation of CCN photocatalytic materials 0.6 g CTAB was dissolved in 60 mL ultrapure water, and 3 g melamine was weighed and added to the above solution, and ultrasonic treatment was performed for 10 min. The mixed solution was transferred to a high-pressure reactor and hydrothermally reacted at 150 °C for 12 h. After the reaction, the product was taken out, washed alternately by centrifugation with ultrapure water and anhydrous ethanol for 3 times, dried at 80 °C and ground into powder. Then, the powder was placed in a muffle furnace and calcined at 550 °C for 4 h at a heating rate of 5 °C / min in an air atmosphere to finally obtain the product CCN. In addition, carbon nitride obtained without CTAB-modified precursor was prepared, which was recorded as CN.
[0030] The X-ray diffraction (XRD) patterns of the CCN and CN nanomaterials prepared in this example are shown in Figure 1 .
[0031] (2) Preparation of PCL@CCN composite film 0.2 g CCN powder was dispersed in 5 mL DMF and ultrasonically treated for 1 h to obtain suspension A. Another 1 g PCL was added to 5 mL DMF and stirred at 60 °C until completely dissolved to obtain solution B. Subsequently, suspension A was poured into solution B and stirred evenly to form a uniform light yellow spinning solution. The prepared spinning solution was transferred to a syringe and electrospun at a positive voltage of 10.8 kV for 8 h. The feed rate of the spinning solution was set to 0.8 mL / h, the distance from the needle to the roller collector was 13 cm, and the roller speed was 90 rpm. During the experiment, the temperature was maintained at 25±5 °C and the humidity was controlled at 30±5%. Finally, the prepared electrospun membrane was dried at 45 °C for 12 h to obtain a PCL@CCN composite membrane.
[0032] The scanning electron microscope (SEM) image of the PCL@CCN nanofiber membrane prepared in this example is shown in Figure 2 .
[0033] (3) Preparation of HPCL@CCN carbon nitride-based photocatalytic oil-water separation composite membrane The membrane was cut into appropriate size, immersed in 50 mL 1 M NaOH solution, and shaken in an oscillation box at 37 °C for 0.5 h to obtain the HPCL@CCN membrane. Finally, the HPCL@CCN composite membrane was dried at 45 °C for 6 h.
[0034] The scanning electron microscope (SEM) image of the HPCL@CCN nanofiber membrane prepared in this example is shown in Figure 3 .
[0035] The water contact angle and oil contact angle of the HPCL@CCN composite film in air are both 0°, showing super-amphiphobicity in air. The oil contact angle under water is 155°, and the water contact angle under oil is 151°, both showing super-amphiphobicity under liquid ( Figure 4 ).
[0036] 2. Application of on-demand separation of oil-in-water emulsion / water-in-oil emulsion The on-demand separation experiment of water-in-oil emulsion / oil-in-water emulsion was carried out using a gravity separation device. The prepared HPCL@CCN composite fiber membrane was wetted with ultrapure water / oil and fixed in the gravity separation device. The on-demand separation of water-in-oil emulsion / oil-in-water emulsion was carried out under gravity drive, and the separation efficiency of water-in-oil was analyzed by a total organic carbon analyzer and the separation efficiency of oil-in-water was analyzed by a Karl Fischer titrator. The separation flux of the water-in-hexane emulsion was measured to be 1972.54 L m -2 h -1 , the separation efficiency is 99.2%; for n-hexane-water emulsion, the separation flux is 925.38 L m -2 h -1 , the separation efficiency is 99.3%; under the action of light, a higher flux recovery rate (90%) is achieved for high-viscosity water-in-crude oil emulsion.
[0037] The prepared HPCL@CCN composite fiber membrane can be rinsed and dried with ethanol to alternately separate water-in-oil emulsion / oil-in-water emulsion, and the separation efficiency is above 99% ( Figure 5 The self-cleaning performance of the prepared membrane was characterized by a four-step filtration test. First, the prepared membrane was used to filter deionized water and the pure water flux (J w , L m −2 h −1 ). Secondly, the membrane was used to separate the water-in-oil emulsion for 5 min to simulate high-viscosity crude oil pollution. The flux at this time was J e (L m −2 h −1 ). The third step is to take out the contaminated membrane and wash it with deionized water for 10 min, and then record the pure water flux (J) of the membrane after static pressure cleaning. r1 , L m −2 h−1 ). In the fourth step, the membrane was moistened with ultrapure water and irradiated with visible light for 60 min, and then the pure water flux of the membrane after photocatalytic self-cleaning was recorded again (J r2 , L m −2 h −1 ). Take the average value for each stage to eliminate the error. The calculation formulas for the flux recovery rate after water washing, the flux recovery rate under light, the reversible pollution resistance and the irreversible pollution resistance are as follows:
[0038]
[0039]
[0040]
[0041] The flux recovery rate, reversible pollution resistance and irreversible pollution resistance of the HPCL@CCN nanofiber membrane prepared in this example under light are shown in the figure. Figure 6 .
[0042] 3. Application of dye degradation A xenon lamp was used as the visible light source (light intensity: 0.3 W cm −2 The prepared HPCL@CCN photocatalytic composite film material (4 cm×4 cm) was immersed in 50 mL of MB aqueous solution (10 ppm) and 50 mM H2O2 was added (255 μL (30% wt%)). The system was then placed in the dark for 30 min to achieve steady-state adsorption equilibrium. Then, the xenon lamp (light power density: 0.3 W / cm 2 ) for 90 min, and the MB concentration was calculated by measuring the absorbance of MB at 664 nm using a UV-visible spectrophotometer. After irradiation with visible light for 90 min, the degradation rate of MB dye by HPCL@CCN was 99.99%. Example 2
[0043] 1. Preparation of HPCL@CCN composite membrane (1) Preparation of CCN photocatalytic materials 0.3 g of CTAB was dissolved in 60 mL of ultrapure water, and 3 g of melamine was weighed and added to the above solution, and ultrasonic treatment was performed for 10 min. The mixed solution was transferred to a high-pressure reactor and hydrothermally reacted at 150 °C for 12 h. After the reaction, the product was taken out, washed alternately by centrifugation with ultrapure water and anhydrous ethanol for 3 times, dried at 80 °C and ground into powder. Then, the powder was placed in a muffle furnace and calcined at 550 °C for 4 h at a heating rate of 5 °C / min in an air atmosphere to finally obtain the product CCN.
[0044] (2) Preparation of PCL@CCN composite film: Same as Example 1.
[0045] (3) Preparation of HPCL@CCN carbon nitride-based photocatalytic oil-water separation composite membrane: Same as Example 1.
[0046] 2. Application of on-demand separation of oil-in-water emulsion / water-in-oil emulsion The separation flux of the HPCL@CCN photocatalytic composite membrane prepared in this embodiment for n-hexane-in-water emulsion was measured by the test method of Example 1 to be 1772.97 L m -2 h -1 , the separation efficiency is 98.8%; for n-hexane-water emulsion, the separation flux is 855.19 L m -2 h -1 The separation efficiency is 98.39%. Under the action of light, a higher flux recovery rate (86.4%) is achieved for high-viscosity water-in-crude oil emulsion.
[0047] 3. Application of dye degradation Referring to the test method of Example 1, after being irradiated with visible light for 90 min, the degradation rate of MB dye by HPCL@CCN was 80.19%. Example 3
[0048] 1. Preparation of HPCL@CCN composite membrane (1) Preparation of CCN photocatalytic materials 0.9 g CTAB was dissolved in 60 mL ultrapure water, and 3 g melamine was weighed and added to the above solution, and ultrasonic treatment was performed for 10 min. The mixed solution was transferred to a high-pressure reactor and hydrothermally reacted at 150 °C for 12 h. After the reaction, the product was taken out, washed alternately by centrifugation with ultrapure water and anhydrous ethanol for 3 times, dried at 80 °C and ground into powder. Then, the powder was placed in a muffle furnace and calcined at 550 °C for 4 h at a heating rate of 5 °C / min in an air atmosphere to finally obtain the product CCN.
[0049] (2) Preparation of PCL@CCN composite film: Same as Example 1.
[0050] (3) Preparation of HPCL@CCN carbon nitride-based photocatalytic oil-water separation composite membrane: Same as Example 1.
[0051] 2. Application of on-demand separation of oil-in-water emulsion / water-in-oil emulsion The separation flux of the n-hexane-in-water emulsion was 1830.21 L m according to the test method of Example 1. -2 h -1 , the separation efficiency is 98.3%; for n-hexane-water emulsion, the separation flux is 872.42 L m -2 h -1 The separation efficiency is 98.69%. Under the action of light, a higher flux recovery rate (82.7%) is achieved for high-viscosity water-in-crude oil emulsion.
[0052] 3. Application of dye degradation Referring to the test method of Example 1, after being irradiated with visible light for 90 min, the degradation rate of MB dye by HPCL@CCN was 83.92%. Example 4
[0053] 1. Preparation of HPCL@CCN composite membrane (1) Preparation of CCN photocatalytic materials 0.6 g CTAB was dissolved in 60 mL ultrapure water, and 3 g melamine was weighed and added to the above solution, and ultrasonic treatment was performed for 10 min. The mixed solution was transferred to a high-pressure reactor and hydrothermally reacted at 150 °C for 24 h. After the reaction, the product was taken out, washed alternately by centrifugation with ultrapure water and anhydrous ethanol for 3 times, dried at 80 °C and ground into powder. Then, the powder was placed in a muffle furnace and calcined at 550 °C for 4 h at a heating rate of 5 °C / min in an air atmosphere to finally obtain the product CCN.
[0054] (2) Preparation of PCL@CCN composite film: Same as Example 1.
[0055] (3) Preparation of HPCL@CCN carbon nitride-based photocatalytic oil-water separation composite membrane: Same as Example 1.
[0056] 2. Application of on-demand separation of oil-in-water emulsion / water-in-oil emulsion Referring to the test method of Example 1, the separation flux of the n-hexane-in-water emulsion was 1845.89 L m -2 h -1 , the separation efficiency is 98.1%; for n-hexane-water emulsion, the separation flux is 838.67 L m -2 h -1The separation efficiency is 97.34% under the action of light, and a higher flux recovery rate (84.19%) is achieved for high-viscosity water-in-crude oil emulsion.
[0057] 3. Application of dye degradation Referring to the test method of Example 1, after being irradiated with visible light for 90 min, the degradation rate of MB dye by HPCL@CCN was 76.13%. Example 5
[0058] 1. Preparation of HPCL@CCN composite membrane (1) Preparation of CCN photocatalytic materials 0.6 g CTAB was dissolved in 60 mL ultrapure water, and 3 g melamine was weighed and added to the above solution, and ultrasonic treatment was performed for 10 min. The mixed solution was transferred to a high-pressure reactor and hydrothermally reacted at 150 °C for 12 h. After the reaction, the product was taken out, washed alternately by centrifugation with ultrapure water and anhydrous ethanol for 3 times, dried at 80 °C and ground into powder. Then, the powder was placed in a muffle furnace and calcined at 600 °C for 4 h at a heating rate of 5 °C / min in an air atmosphere to finally obtain the product CCN.
[0059] (2) Preparation of PCL@CCN composite film: Same as Example 1.
[0060] (3) Preparation of HPCL@CCN carbon nitride-based photocatalytic oil-water separation composite membrane: Same as Example 1.
[0061] 2. Application of on-demand separation of oil-in-water emulsion / water-in-oil emulsion Referring to the test method of Example 1, the separation flux of the n-hexane-in-water emulsion was 1868.39 L m -2 h -1 , the separation efficiency is 99%; for n-hexane-water emulsion, the separation flux is 819.27 L m -2 h -1 The separation efficiency is 98.97%. Under the action of light, a higher flux recovery rate (84.1%) is achieved for high-viscosity water-in-crude oil emulsion.
[0062] 3. Application of dye degradation Referring to the test method of Example 1, after being irradiated with visible light for 90 min, the degradation rate of MB dye by HPCL@CCN was 92.55%. Example 6
[0063] 1. Preparation of HPCL@CCN composite membrane (1) Preparation of CCN photocatalytic material: same as in Example 1.
[0064] (2) Preparation of PCL@CCN composite film 0.1 g CCN powder was dispersed in 5 mL DMF and ultrasonically treated for 1 h to obtain suspension A. Another 1 g PCL was added to 5 mL DMF and stirred at 60 °C until completely dissolved to obtain solution B. Subsequently, suspension A was poured into solution B and stirred evenly to form a uniform light yellow spinning solution. The prepared spinning solution was transferred to a syringe and electrospun at a positive voltage of 10.8 kV for 8 h. The feed rate of the spinning solution was set to 0.8 mL / h, the distance from the needle to the roller collector was 13 cm, and the roller speed was 90 rpm. During the experiment, the temperature was maintained at 25±5 °C and the humidity was controlled at 30±5%. Finally, the prepared electrospun membrane was dried at 45 °C for 12 h to obtain a PCL@CCN composite membrane.
[0065] (3) Preparation of HPCL@CCN carbon nitride-based photocatalytic oil-water separation composite membrane: Same as Example 1.
[0066] 2. Application of on-demand separation of oil-in-water emulsion / water-in-oil emulsion Referring to the test method of Example 1, the separation flux of the n-hexane-in-water emulsion was 1903.24 L m -2 h -1 , the separation efficiency is 98.57%; for n-hexane-water emulsion, the separation flux is 881.44 L m -2 h -1 The separation efficiency is 98.11%. Under the action of light, a higher flux recovery rate (76.3%) is achieved for high-viscosity water-in-crude oil emulsion.
[0067] 3. Application of dye degradation Referring to the test method of Example 1, after being irradiated with visible light for 90 min, the degradation rate of MB dye by HPCL@CCN was 84.27%. Example 7
[0068] 1. Preparation of HPCL@CCN composite membrane (1) Preparation of CCN photocatalytic material: same as in Example 1.
[0069] (2) Preparation of PCL@CCN composite film 0.2 g CCN powder was dispersed in 5 mL DMF and ultrasonically treated for 1 h to obtain suspension A. Another 2 g PCL was added to 5 mL DMF and stirred at 60 °C until completely dissolved to obtain solution B. Subsequently, suspension A was poured into solution B and stirred evenly to form a uniform light yellow spinning solution. The prepared spinning solution was transferred to a syringe and electrospun at a positive voltage of 10.8 kV for 8 h. The feed rate of the spinning solution was set to 0.8 mL / h, the distance from the needle to the roller collector was 13 cm, and the roller speed was 90 rpm. During the experiment, the temperature was maintained at 25±5 °C and the humidity was controlled at 30±5%. Finally, the prepared electrospun membrane was dried at 45 °C for 12 h to obtain a PCL@CCN composite membrane.
[0070] (3) Preparation of HPCL@CCN carbon nitride-based photocatalytic oil-water separation composite membrane: Same as Example 1.
[0071] 2. Application of on-demand separation of oil-in-water emulsion / water-in-oil emulsion Referring to the test method of Example 1, the separation flux of the n-hexane-in-water emulsion was 1574.33 L m - 2 h -1 , the separation efficiency is 97.48%; for n-hexane-water emulsion, the separation flux is 798.86 L m -2 h -1 The separation efficiency is 98.71%. Under the action of light, a higher flux recovery rate (81.4%) is achieved for high-viscosity water-in-crude oil emulsion.
[0072] 3. Application of dye degradation Referring to the test method of Example 1, after being irradiated with visible light for 90 min, the degradation rate of MB dye by HPCL@CCN was 90.6%. Example 8
[0073] 1. Preparation of HPCL@CCN composite membrane (1) Preparation of CCN photocatalytic material: same as in Example 1.
[0074] (2) Preparation of PCL@CCN composite film: Same as Example 1.
[0075] (3) Preparation of HPCL@CCN carbon nitride-based photocatalytic oil-water separation composite membrane The membrane was cut into appropriate size, immersed in 50 mL 1 M NaOH solution, and oscillated in an oscillation box at 37 °C for 0.1 h to obtain the HPCL@CCN membrane. Finally, the HPCL@CCN composite membrane was dried at 45 °C for 6 h.
[0076] 2. Application of on-demand separation of oil-in-water emulsion / water-in-oil emulsion Referring to the test method of Example 1, the separation flux of the n-hexane-in-water emulsion was 1366.59 L m -2 h -1 , the separation efficiency is 98.16%; for n-hexane-water emulsion, the separation flux is 896.44 L m -2 h -1 The separation efficiency is 99.2%. Under the action of light, a higher flux recovery rate (79.3%) is achieved for high-viscosity water-in-crude oil emulsion.
[0077] 3. Application of dye degradation Referring to the test method of Example 1, after being irradiated with visible light for 90 min, the degradation rate of MB dye by HPCL@CCN was 97.9%. Example 9
[0078] 1. Preparation of HPCL@CCN composite membrane (1) Preparation of CN photocatalytic materials Weigh 3 g of melamine and add it to the above solution, and ultrasonically treat it for 10 min. Transfer the mixed solution to a high-pressure reactor and hydrothermally react it at 150 °C for 12 h. After the reaction, take out the product, wash it three times with ultrapure water and anhydrous ethanol, dry it at 80 °C and grind it into powder. Then, place the powder in a muffle furnace, calcine it at 550 °C for 4 h at a heating rate of 5 °C / min in an air atmosphere, and finally grind it into powder, which is recorded as CN.
[0079] (2) Preparation of PCL@CN composite film: Same as Example 1.
[0080] (3) Preparation of HPCL@CN carbon nitride-based photocatalytic oil-water separation composite membrane: Same as Example 1.
[0081] 2. Application of on-demand separation of oil-in-water emulsion / water-in-oil emulsion Referring to the test method of Example 1, the separation flux of the n-hexane-in-water emulsion was 1819.79 L m -2 h -1 , the separation efficiency is 98.92%; for n-hexane-water emulsion, the separation flux is 878.47 L m -2 h -1 The separation efficiency is 98.51%. Under the action of light, a higher flux recovery rate (85.2%) is achieved for high-viscosity water-in-crude oil emulsion.
[0082] 3. Application of dye degradation Referring to the test method of Example 1, after being irradiated with visible light for 90 min, the degradation rate of MB dye by HPCL@CCN was 84.63%.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A carbon nitride-based photocatalytic composite film, characterized in that: The carbon nitride-based photocatalytic composite membrane is a nanofiber membrane prepared by blending modified carbon nitride with a high molecular polymer and a solvent; the modified carbon nitride is prepared by thermal decomposition of a melamine precursor modified by hexadecyltrimethylammonium bromide; and the high molecular polymer is polycaprolactone.
2. The carbon nitride-based photocatalytic composite film according to claim 1, characterized in that: The solvent is N,N, dimethylformamide; the mass ratio of the modified carbon nitride, the high molecular polymer and the solvent is 0.1-0.5:0.5-2:9-10.
3. The method for preparing the carbon nitride-based photocatalytic composite film according to claim 1 or 2, characterized in that: The steps include: The modified carbon nitride powder is uniformly dispersed in a solvent to obtain a suspension A; a polymer is dissolved in a solvent to obtain a solution B; the suspension A is poured into the solution B and stirred uniformly to obtain a spinning solution; and a PCL@CCN composite film is prepared by electrospinning; The membrane was cut into appropriate size, immersed in NaOH solution, oscillated in an oscillation box at 37 °C for 0.1-1 h, and dried to obtain the HPCL@CCN membrane.
4. The method for preparing the carbon nitride-based photocatalytic composite film according to claim 3, characterized in that: The electrospinning is as follows: electrospinning is performed at a positive voltage of 10-12 kV for 8-10 h; the feeding rate of the spinning solution is set to 0.8-1 mL / h, the distance from the needle to the roller collector is 10-13 cm, and the roller speed is 90 rpm.
5. The method for preparing the carbon nitride-based photocatalytic composite film according to claim 3, characterized in that: The concentration of the NaOH solution is 1 mol / L.
6. The method for preparing the carbon nitride-based photocatalytic composite film according to claim 3, characterized in that: The modified graphite carbon nitride is prepared by the following method: dissolving hexadecyltrimethylammonium bromide in water, adding melamine, and uniformly dispersing by ultrasonication to obtain a mixed solution; subjecting the mixed solution to a hydrothermal reaction at 150°C for 6-24 hours, and after the reaction is completed, washing, drying, and grinding the product into powder; calcining the powder at 500-600°C for 4 hours at a heating rate of 5°C / min in an air atmosphere to obtain a product-modified carbon nitride; wherein the mass ratio of hexadecyltrimethylammonium bromide to melamine is 0.3-0.9:
3.
7. The method for preparing the carbon nitride-based photocatalytic composite film according to claim 6, characterized in that: The washing is performed by alternating centrifugal washing with ultrapure water and anhydrous ethanol for 3 times; and / or the drying temperature is 70-80°C.
8. Use of the carbon nitride-based photocatalytic composite membrane according to claim 1 or 2 in oil-water separation and photocatalytic degradation of dyes.
Citation Information
Patent Citations
Preparation method for super-hydrophobic SiO2 aerogel film
CN103755152A
High-light-transmittance photovoltaic module and preparation method thereof
CN117624666A
Preparation method and application of FeOOH quantum dot modified amino-rich porous ultrathin g-C3N4 photo-Fenton water purification material
CN117732496A
Acid gas separation layer, production method and facilitated transport membrane therefor, and acidic gas separation module and acidic gas separation system
JP2014065034A
Separation module, method for producing separation module, tube body, and winding misalignment prevention member
WO2014051117A1